Analisis Peran Sumber Daya Manusia Dalam Pengembangan Pariwisata di Desa Wisata Margacinta Kecamatan Cijulang Kabupaten Pangandaran - Iskandar, Ridwan (Jurnal Akademi Pariwisata Medan, 2024)
In tourism development, one thing that has a very important role is the Human Resources (HR) aspect. Success in tourism management and development requires quality human resources, which are expected to be able to provide added value to the community at a tourist attraction. Tourism Human Resources includes several stakeholders including tourists/tourists and workers (employment). The development of tourist attractions requires the role of all parties. This research aims to provide an overview of the extent of the role of human resources owned by the Margacinta Tourism Village in efforts to develop its tourism village. This research uses a descriptive qualitative approach and uses technical analysis using interviews, observation and literature study. The results of the research concluded that the human resources owned by the Margacinta Tourism Village have played a sufficient role, but there is a need for coaching and guidance in efforts to develop the Margacinta Tourism Village in the future.